2014
DOI: 10.1021/jp507196q
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding and Related Properties in Liquid Water: A Car–Parrinello Molecular Dynamics Simulation Study

Abstract: The local hydrogen bonding structure and dynamics of liquid water have been investigated using the Car-Parrinello molecular dynamics simulation technique. The radial distribution functions and coordination numbers around water molecules have been found to be strongly dependent on the number of hydrogen bonds formed by each molecule, revealing also the existence of local structural heterogeneities in the structure of the liquid. The results obtained have also revealed the strong effect of the local hydrogen bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
70
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 83 publications
18
70
1
Order By: Relevance
“…In the present case, the positions of the peaks fall between 100 to 200 cm −10 below the experimental frequencies, consistently with previous Car-Parrinello simulations of H 2 O [51,52].…”
Section: Bulk Phase Propertiessupporting
confidence: 93%
See 1 more Smart Citation
“…In the present case, the positions of the peaks fall between 100 to 200 cm −10 below the experimental frequencies, consistently with previous Car-Parrinello simulations of H 2 O [51,52].…”
Section: Bulk Phase Propertiessupporting
confidence: 93%
“…Its shape does not seem to be converged, probably because insufficient sampling: note that in this case the RDF is built from a single water molecule out of 64. Various studies of liquid water using the Car-Parrinello method with GGA functionals and an electronic mass comparable to the one employed here, have found overstructured oxygen-oxygen RDFs at room temperature and pressure [42,52,55,56], suggesting that in these conditions this approach represents bulk water in a glassy or supercooled state. Data from one of these works is depicted in Figure 4.…”
Section: Bulk Phase Propertiesmentioning
confidence: 76%
“…Interestingly, some members of the design output ensemble do not contain the hydrogen bond between Histidine 341 and Threonine P -2 , consistent with observations of hydrogen bond breaking and reformation from experimental 81 and MD simulation [82][83][84][85] studies. Indeed, solution NMR studies of ubiquitin showed that threonine residues occupy multiple rotameric states.…”
Section: With 6ov7 To Determinesupporting
confidence: 78%
“…We show that our method, which we call "monomer PIMD", correctly captures changes in the structure of water found in a full PIMD simulation but at much lower computational cost.There is great interest in being able to accurately simulate liquid water at the quantum mechanical level. [1][2][3][4] The most widely used methodology for this is density functional theory. However, many density functionals fail to accurately reproduce all of the key properties of water such as its density, compressibility, and diffusion constant.…”
mentioning
confidence: 99%